Biopsychosocial Approach to the Analysis of Self-Injurious Behavior in Young Individuals - Dzeruzhynska Наталія; Rudenko Єлизавета (Psychosomatic Medicine and General Practice, 2025)
Introduction. Nonsuicidal self-injury (NSSI) is a complex phenomenon predominantly observed in young individuals and is associated with an increased risk of affective and anxiety disorders, impulsivity, and suicidal behavior. The biopsychosocial nature of this behavior necessitates a comprehensive investigation of the biological, psychological, and social determinants contributing to its onset and progression. Objective. To identify the key biological, psychological, and social factors associated with the development of NSSI in young individuals through a comprehensive analysis of mental state, coping strategies, perceived social support, self-compassion, and affective symptoms. Materials and Methods. The empirical study was conducted in 2024–2025 at the Municipal Psychiatric Dispensary and the Odesa Regional Mental Health Center in Odesa, Ukraine. The sample included 34 individuals aged 16–30 years with documented signs of self-injurious behavior. Standardized psychodiagnostic tools were employed (HADS, CD-RISC-10, SCS-SF, MSPSS, Eysenck’s method), along with a custom questionnaire. Statistical analysis was performed using descriptive, correlational, and regression methods in SPSS 27. Results. Key determinants of self-injurious behavior were identified as high levels of trauma exposure, emotional dysregulation, low self-compassion, and insufficient social support. The sample was characterized by moderate-to-low resilience, elevated anxiety and aggression, and the predominance of maladaptive coping strategies, particularly avoidance and self-control. Conclusions. Findings indicate that NSSI in young individuals has a multifactorial nature, resulting from the interaction of affective disorders, emotional dysregulation, social determinants, and biological vulnerabilities. Regression analysis confirmed the predictive value of trauma exposure, psychological factors, and emotion regulation in explaining NSSI risk, while high self-compassion was identified as a protective factor. Correlational analysis revealed strong associations between the frequency of NSSI episodes and psychological and social determinants. Psychosocial profiling highlighted the prevalence of anxiety, aggression, maladaptive coping, and low social support, indicating the ineffectiveness of psychological self-regulation mechanisms.